A chiral ion-pair photoredox organocatalyst: enantioselective anti-Markovnikov hydroetherification of alkenols. Issue 6 (21st February 2017) - Yang, Zhongbo; Li, Han; Li, Sujia; Zhang, Ming-Tian; Luo, Sanzhong
Abstract : A chiral ion-pair photoredox organocatalyst was reported to facilitate visible-light-meditated asymmetric anti-Markovnikov hydroetherification of alkenols with high reactivity and moderate enantioselectivity. Abstract : A chiral ion-pair photoredox organocatalyst was reported to facilitate visible-light-meditated asymmetric anti-Markovnikov hydroetherification of alkenols with high reactivity and moderate enantioselectivity.